(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2014)
Observers have longbelieved that commuting to and from urban places well served by transit is moreenergy efficient than commuting to more auto-oriented suburban work sites.However, little empirical investigation has been conducted to substantiate thishypothesis. An analysis of commutation patterns for two locations in Delhi– oneurban and one suburban – provides strong evidence that, in the aggregate,workers commuting to urban places consume significantly less energy than thosecommuting to suburban locations. The paper attemptsto highlight the need for a cogent urban transport policy without which therewill be ad hoc interventions. Such interventions, apart from not adding up to acomprehensive approach, will result in greater confusion. Furthermore, itemphasizes that if there is no worthwhile public transport, it will still needto be reinvented to promote a better quality of life. The need of the hour isformulation of an urban transport strategy that is both pragmatic and holisticin its approach.